Validitas Konstruk (CFA) dan Model Rasch Alat Ukur Regulasi Diri untuk Anak Usia 3-7 tahun - Salsabila Fitrizqi; Hery Susanto (PAUDIA : Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2021)
AbstractChildren’s self-regulation is the child’s ability to manage emotions and focus their attention on controlling behavior so that they behave in accordance with environmental demands. Children’s self-regulation consists of 3 aspects, namely cognitive regulation, emotional regulation, and behavioral regulation. Children’s self-regulation is related to the child’s well-being during the transition from childhood to adolescents. Self-regulation is also an important aspect in seeing school readiness. Measurement of children’s self-regulation usually uses observation methods with games such as HTKS (head-toes-knees-shoulder) or delay gratification, which can be situational and subjective comparing with parental observations of children’s daily behavior. The aim of this study was to get standardized measuring tools for children’s self-regulation in Indonesia. The participants of this study were parents whose has child aged 3-7 years old. Data obtained from 313 participants. Data analysis by construct validity (CFA) and Rasch Model utilize Lisrel student version 9.30 and winstep ver.3.73 programs. Reliability instrument children’s self-regulation classified to excellent with α = 0.99, validity construct using CFA meet the criteria.  It can be concluded that a children self-regulation model can be utilize as a valid test to evaluate targeted construct and the instrument fit to rasch models.Keywords: measurement, self-regulation, preschoolAbstrakRegulasi diri anak adalah kemampuan anak dalam mengelola emosi dan fokus perhatiannya untuk mengendalikan perilaku, agar berperilaku sesuai dengan tuntutan lingkungan. Regulasi diri anak terdiri dari 3 aspek, yaitu, regulasi kognitif, regulasi emosi, dan regulasi perilaku. Kemampuan regulasi diri anak masa awal berkaitan dengan kesejahteraan pada masa transisi anak-anak ke remaja. Kemampuan kesiapan sekolah anak dapat dilihat melalui aspek regulasi diri. Pengukuran regulasi diri anak biasanya menggunakan metode observasi dengan permainan seperti KPLK (kepala-pundak-lutut-kaki) atau penundaan kepuasan yang dapat menjadi situasional dan subjektif dibandingkan penilaian melalui observasi orang tua mengenai perilaku anak sehari-hari. Penelitian ini bertujuan untuk memperoleh instrumen regulasi diri anak yang terstandardisasi di Indonesia. Partisipan penelitian adalah orang tua yang memiliki anak berusia 3-7 tahun, diperoleh data 313 partisipan. Analisis data menggunakan validitas konstruk dan pendekatan model rasch dibantu oleh program Lisrel student ver. 9.30 dan winstep ver. 3.73. Diperoleh nilai reliabilitas total instrumen alat ukur tergolong sangat tinggi dengan α = 0.99, nilai validitas konstruk (CFA) memenuhi kriteria. Dapat disimpulkan bahwa model regulasi diri anak dapat digunakan sebagai tes yang valid untuk mengukur konstruk yang ditargetkan dan instrumen sesuai dengan model rasch.Kata kunci: alat ukur, regulasi diri, prasekolah